PENGARUH PENGGUNAAN METODE HYPNOTEACHING TERHADAP EMOTIONAL INTELLEGENCE ANAK USIA 3 â 4 TAHUN DI KELOMPOK BERMAIN TUNAS HARAPAN TULUNGAGUNG - Rohmadheny, Prima Suci (Jurnal CARE (Children Advisory Research and Education), 2013)
The research was motivated by emotional problems that happened in Playgroup Tunas Harapan Tulungagung. Emotional problems at an early childhood like in there, it would lead to further emotional problems at adults such as suicide. This is a reflection of the low emotional intelligence condition. Objectives to be achieved in this study was to determine whether there is an effect of applying hypnoteaching method on emotional intelligence of children aged 3-4 years in Tunas Harapan Playgroup Tulungagung. This method involves working with the subconscious mind, giving positive suggestions about emotion to the children when they are in a state of relaxation and focus and make learning fun for children. This study uses a type of quantitative approach with pre-experimental research The One-Group Pretest-posttest design. Data collection methods used were observation to determine changes in the emotional intelligence of children. The subjects of this study were four teen students from Tunas Harapan Playgroup as a whole Tulungagung. Techniques of data analys is techniques used are non-parametric statistical analysis using Wilcoxon test marked level. From the calculation results obtained Thitung<Ttabel. This is means that the hypothesis of the study, which reads "hypnoteaching method has a significant effect on the emotional intelligence of children aged 3 â 4 years in Tunas Harapan Play Group Tulungagung " is acceptable.Key words : hypnoteaching method, emotional intelligence